Dari Diam Menjadi Agensi: Membingkai Ulang Tantangan Pendidikan Pascasarjana Indonesia di Inggris - Haryono, Aloysia Karina; Sheridan, Louise (ANIMA Indonesian Psychological Journal, 2025)
This study critically re-examines the academic struggles of Indonesian postgraduate students in the United Kingdom (UK), drawing on empirical data from a prior qualitative study. The study employs a dual theoretical lens from Freire's Pedagogy of the Oppressed and Bandura's Social Cognitive Theory of Human Agency, grounded in a critical realist ontology, to explore the underlying structural forces of how academic practices contribute to student's educational experiences. Three interrelated themes are developed: (1) silence and pedagogical disempowerment; (2) destabilization of self-efficacy within unfamiliar academic conventions; and (3) the tension between agentic aspiration and marginalization. The findings challenge neoliberal assumptions of meritocracy and call for more awareness, reflexive, and humanizing approaches to international education that treat students not as culturally deficient or individually lacking but as subjects shaped by and capable of transformation within and against inherited educational systems.